PENGARUH PRODUK WISATA DAN WORD OF MOUTH TERHADAP KEPUTUSAN BERKUNJUNG (Studi Kasus pada Pengunjung Objek Wisata Pantai Klayar) - Ilham Ramadhan; Hari Susanta Nugraha (Jurnal Ilmu Administrasi Bisnis, 2016)
Tourism has become the largest industry and show consistent growth over the years, his specialty in East Java province. One of these attractions Klayar Beach in Pacitan that have unique tourism potential. However, the number of tourist arrivals from 2010 to 2015 relatively volatile and tend to decrease in the percentage of development. While the survey, in getting the visitor complaints against travel products, It is fear for the existence of negative information spread among travelers.This study aims to determine the influence of Tourism Products, and Word of Mouth to the Decision to Visit Attractions Klayar Beach. This type of research is explanatory research, in which the data collection techniques used is by means of questionnaire, the selected sample of 100 people with accidental sampling and purposive sampling. Respondents are visitor attractions Klayar Beach who had visited the beach Klayar.The results showed that the Tourism Product and significant effect on the Decree viewed by contributing 24.3% and the rest is explained by other factors. Word of Mouth influential and significant to the Decree viewed by contributing 11.8% and the rest is explained by other factors. Meanwhile, simultaneously Tourism Products and Word of Mouth influential and significant to the Decision of Been. That is, the better the Tourism Product and Word of Mouth, the higher the Decision to Visit Attractions Klayar Beach. Additionally Travel Products has the most dominant influence with regression coefficient of 0.350. The results obtained by analyzing primary data using validity, reliability test, correlation coefficient, determination coefficient, simple linear regression, multiple linear regression, and a significance test (t test and F) with SPSS 16.0.Based on this, the researchers suggest that managers Attractions Pantai Klayar further improve the tourism product, which adds to public transportation, parking area, repair facilities and more active in offering information to visitors facilities, so as to increase tourist arrivals in Turkish Klayar.